PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATERI PECAHAN UNTUK MENINGKATKAN MINAT BELAJAR MATEMATIKA SISWA KELAS III SEKOLAH DASAR - Ratnawati; Suci Rahma Putri; Desri Irsanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of this research is to develop interactive learning media on fraction material to increase interest in learning mathematics for third grade elementary school students. The type of research that the author uses in this research is research and development. The ADDIE model is an abbreviation for Analyze, Design, Development, Implementation and Evaluation. The type of data used in this research is qualitative and quantitative. The data collection techniques used were interviews, observation and documentation. Then the data analysis technique used uses validity analysis, practicality analysis and effectiveness analysis. The results obtained in this research validated interactive learning media by three expert validators. The results of this validation show that interactive learning media obtained a final percentage result of 96% in the Valid category. Then in terms of practicality, the score from the teacher response questionnaire and student questionnaire, the final result from the teacher response questionnaire was 98% and the class III student response at SDN 05 Koto Baru was 94% in the very practical category. Then the effectiveness is assessed from student learning outcomes. The learning outcomes of class III students at SDN 05 Koto Baru completed 15 students who obtained a percentage of 94% in the very effective category.